Tinjauan Terhadap Implementasi Enterprise Architecture: Analisis Perbandingan Studi Kasus Industri Kesehatan - Chandra, Carissa; Young, Jian; Salim, Jodie; Onggie, Karen; Kimberly; Andriano, Vinson (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This paper discusses the review of the implementation of EA (Enterprise Architecture) in the healthcare industry through a comparative analysis of case studies using two frameworks namely TOGAF ADM and Zachman. The purpose of writing this paper is to identify the strengths and weaknesses of the implementation of each case study, as well as provide an understanding of the use of frameworks in the health industry. The type of analysis in this paper is a qualitative analysis using five papers containing case studies from different health companies which implement the ADM and Zachman TOGAF framework. The results of the analysis show that the two frameworks have different approaches in dealing with certain challenges and needs of the healthcare industry. In addition, there is the use of a matrix, namely the TOGAF framework which aims to provide an overview of the relationships and dependencies between the elements of the two frameworks. After doing the analysis and matrix, it can be concluded that the two frameworks are able to influence EA in the health industry. Thus, making it easier for companies to plan, design, manage, and implement enterprise architecture in an effective and efficient manner.